Does footwear influence countermovement jump parameters used to assess performance in collegiate basketball players? - Heishman, A. D.; Peak, K. M.; Daub, B. D.; Miller, R. M.; Freitas, E. D. (International Journal of Kinesiology & Sports Science, 2021)
Background: The countermovement jump (CMJ) is used to monitor short- and long-term changes in neuromuscular performance, where practically relevant alteration may be subtle, requiring detailed and consistent testing protocols to limit error and allow detection of meaningful change. Collegiate basketball players often wear different types of footwear depending upon the training activity, potentially influencing CMJ performance outcomes. Objective: This study evaluated the influence of footwear on key CMJ variables used for routine performance assessments in a cohort of 11 NCAA women`s collegiate basketball players. Method: In a cross-over repeated measures study design, players performed three CMJs in Basketball-, Training-(Trainers), and Olympic Weightlifting (WL) shoes, in a randomized order during one testing session. One-way repeated measures analyses of variance (p = .05) and effect sizes (Cohen`s d) were used to discern differences in CMJ variables among shoe conditions. Results: WL demonstrated greater Eccentric Mean Force (p = .014, d = 0.03) and lower Flight Time:Contraction Time (p = .029, d = 0.31), Jump Height (p = .040, d = 0.32), and Reactive Strength Index-Modified (p = .032, d = 0.40) than both Basketball and Trainers. Additionally, WL exhibited lower Concentric Mean Force (p = .018, d = 0.19), Concentric Mean Power (p = .008, d = 0.29), Eccentric Peak Force (p = .050, d = 0.19), and Flight Time (p = .036, d = 0.31) compared to Trainer. No significant differences and only trivial effects appeared between Basketball and Trainers (p > 0.05, d < 0.1). Conclusion: These findings suggest footwear significantly influences CMJ performance. WL shoes appear to negatively impact CMJ performance; however, Basketball and Trainers appear to exert negligible effects that should allow clinicians and practitioners to feel confident about measurement and data quality when performing short- and long-term CMJ measurements in either Basketball or Trainers